AB0834-HPR Health-related physical fitness testing in physiotherapy practice – reference values. (23rd January 2014) - Tveter, A. T.; Moseng, T.; Dagfinrud, H.; Holm, I.
Abstract : Background: People with musculoskeletal conditions (MSCs) tend to be less physically active 1 and more deconditioned than healthy controls 2 . Recommendations for management of MSCs emphasize exercise as an important part of the treatment 3 . According to current recommendations, patients should be offered an individually tailored exercise program focusing on health-related physical fitness 4 . To improve the clinical usefulness of fitness-measures capturing the patients physical fitness, relevant reference values for these instruments are needed. Objectives: The objective was to establish reference values and distribution of scores for frequently used measures of health-related physical fitness derived from age- and gender-groups of the general population. Methods: In a cross-sectional study, 370 males and females 18-90 years of age were recruited. Five tests (6 min walk test, stair test, handgrip test, 30 sec sit-to-stand test and modified fingertip-to-floor test) and two questionnaires (Physical fitness questionnaire and COOP/WONCA) were included. Results: Performance on all tests, except the modified fingertip-to-floor test, were stable until about 50 years of age, later performance was reduced with increasing age. Responses on patient-reported instrument were stable with gender and age. Distribution of scores are presented i Kernel plots. Image/graph: Conclusions: The reference values can improve the interpretability and clinical usefulness of fitness measures. References: Farr et al. Physical activity levels in patients with early knee osteoarthritis measured by accelerometry. Arthr Rheum 2008; 59(9):1229-1236. Hodselmans et al. Nonspecific chronic low back pain patients are deconditioned and have an increased body fat percentage. Int J Rehabil Res 2010; 33(3):268-270. Hochberg et al. American College of Rheumatology 2012 recommendations for the use of nonpharmacologic and pharmacologic therapies in osteoarthritis of the hand, hip, and knee. Arthr Care Res 2012; 64(4):465-474. Nelson et al. Physical activity and public health in older adults: recommendation from the ACSM and the AHA. Med Sci Sports Exerc 2007; 39(8):1435-1445 Disclosure of Interest: None Declared